2004
DOI: 10.1109/tgrs.2004.834633
|View full text |Cite
|
Sign up to set email alerts
|

Microwave scattering from mixed-species forests, Queensland, Australia

Abstract: Lucas, Richard, Moghaddam, M., Cronin, N., (2004) 'Microwave scattering from mixed-species forests, Queensland, Australia', IEEE Transactions on Geoscience and Remote Sensing 42(10) pp.2142-2159 RAE2008The potential of synthetic aperture radar (SAR) data for retrieving the above-ground and component (e.g., branch, trunk) biomass of mixed-species forests (including woodlands) typical to subtropical Queensland, Australia, was evaluated using a wave scattering model based on that of Durden et al. (1989). The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 29 publications
3
63
0
1
Order By: Relevance
“…Overall, modeling results agree in that with increasing radar wavelength, the scattering from larger tree constituents gains importance; nonetheless, the modeled backscatter signal was hardly dominated by a single scatterer type/backscatter contribution consistently in all of the studies surveyed [64,[68][69][70][71]. As a result, scattering theory suggested that:…”
Section: Approaches For Estimating the Biomass In Trunks Branches Ansupporting
confidence: 56%
“…Overall, modeling results agree in that with increasing radar wavelength, the scattering from larger tree constituents gains importance; nonetheless, the modeled backscatter signal was hardly dominated by a single scatterer type/backscatter contribution consistently in all of the studies surveyed [64,[68][69][70][71]. As a result, scattering theory suggested that:…”
Section: Approaches For Estimating the Biomass In Trunks Branches Ansupporting
confidence: 56%
“…As for models, it was observed throughout the experimental procedure that the backscattering behavior pattern differs in relation to volume measured depending on which family of species is being monitored. As a result, two approaches were defined: for pine trees a semi-empirical WCM model was employed; in the case of eucalyptus trees, a previous study was conducted on eucalyptus groves (Lucas et al, 2004) which showed that by using the L-band PALSAR sensor a linear regression model was what best correlated backscatter with ground truth in these masses; throughout the project it was evidenced that the same applies to Holm oak groves, so a linear regression model was also used.…”
Section: Methodological Approachmentioning
confidence: 99%
“…These models do not explain a system, but provide a relationship between variables derived from a base table. Lucas et al, 2004, showed that they were suitable to estimate structural variables using the C, L and P bands. In this study, an empirical model has proved satisfactory for Eucalyptus groves.…”
Section: Introductionmentioning
confidence: 99%
“…Longer L-band (e.g. L-band 15-20 cm) microwaves have a greater likelihood of penetrating the foliage and small branches at the upper canopies of the forest, and interacting with woody trunks and larger branch components as well as the underlying surface [14,15]. It has been proven that radar is sensitive to the structure of the canopy.…”
Section: Introductionmentioning
confidence: 99%